Pendekatan Pembinaan Karakter Siswa Melalui Program Diniyah MIN 1 Banda Aceh - Murtaza Rahmi (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
The Diniyah program is one of the programs initiated by the Banda Aceh City government to assist schools in internalizing the value of Islamic education to students. Through this program, it is hoped that there will be improvements in student behavior or character in the future. The research objective was to see how the implementation, approaches, opportunities, and challenges of character building for students at MIN 1 Banda Aceh. This study used a qualitative approach with the research subjects of the head, teachers, and students of MIN 1 Banda Aceh. Data collection was carried out by means of observation, interviews, and documentation. The results showed that the stages of the Diniyah program implementation were carried out through a) Al-Qur'ān reading and writing program, b) Increasing memorization and muraja'ah, c) Increasing daily prayer memorization programs, d) Increasing understanding of the contents of the book, e) Increasing the understanding student worship, f) increasing student moral development, which is carried out in the classroom and outside the classroom. The approaches taken include a) awareness approach, b) habituation, c) modeling. There is an opportunity for students to have the maximum time to complete the character-building program properly and schools can improve the quality of the school for the better. The challenges include lack of family support, environment, student readiness, lack of facilities, and several other internal school conditions.